Comparison of Osteoinductive Potential of Autografts vs. Allografts in Mandibular Defect Models - Pratap Movaniya; Ritu Chhatbar; Sumit Bhatt; Ngangbam Johnson Sing; Ashtha Arya; Hiral Parmar (Journal of Pharmacy and Bioallied Sciences)
Background: Mandibular defects resulting from trauma, tumors, or congenital anomalies present a significant challenge in craniofacial reconstruction. Bone grafting, including autografts and allografts, is a widely used approach to repair such defects. Autografts, harvested from the patient’s own body, are considered the gold standard due to their osteogenic, osteoconductive, and osteoinductive properties. However, the limited availability and donor site morbidity have encouraged the use of allografts. Materials and Methods: A total of 40 mandibular defect models in rabbits were divided into two groups: Group A (n = 20) treated with autografts and Group B (n = 20) treated with allografts. Standardized 5 mm × 3 mm defects were created bilaterally in the mandible under general anesthesia. Bone grafts were prepared and placed in the defects. Osteoinductive potential was evaluated over 8 weeks using radiographic analysis, histomorphometric assessment, and quantification of bone formation markers, such as osteocalcin and alkaline phosphatase. Arbitrary scores of bone density and new bone formation were measured at 4 and 8 weeks. Results: At 4 weeks, Group A (autografts) showed significant bone formation with an average bone density score of 65%, compared with 45% in Group B (allografts) (P < 0.05). By 8 weeks, Group A demonstrated an 85% mean bone density, with complete defect bridging observed in 70% of cases. Group B exhibited delayed bone regeneration, with 65% mean bone density and complete bridging in 40% of cases. Histomorphometric analysis revealed higher osteoblast activity and greater bone volume in the autograft group. Osteocalcin levels were notably higher in Group A (120 ng/mL) compared with Group B (95 ng/mL), confirming superior osteoinductive activity. Conclusion: Autografts demonstrated superior osteoinductive potential compared with allografts in mandibular defect models, as evidenced by earlier and more complete bone regeneration. Although allografts remain a viable alternative, their delayed healing response highlights the need for further improvements in graft preparation and bioengineering. Autografts continue to be the preferred choice for mandibular reconstruction when feasible.